2014
DOI: 10.1103/physrevb.90.144403
|View full text |Cite
|
Sign up to set email alerts
|

Spin waves in the anisotropic fcc kagome antiferromagnet

Abstract: Spin wave calculations demonstrate that the macroscopic continuous degeneracy associated with the two-dimensional kagome Heisenberg spin lattice persists in the case of the stacked fcc structure giving rise to zero energy modes in three dimensions. The addition of an effective local cubic anisotropy is shown to remove this continuous degeneracy and introduce a gap in the spectrum as well as modify the inelastic scattering function $S({\bf q},\omega)$. This scenario supports earlier Monte Carlo simulations whic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 38 publications
1
13
0
Order By: Relevance
“…The most popular compound for use as the antiferromagnet in spin valves for magnetic recording is IrMn 3 , which in its ordered crystalline fcc phase is composed of ABC stacked [111] planes of magnetic Mn ions on kagome sites. 4,5,[11][12][13][14][15] The large number of studies over the past few decades on the near-neighbor antiferromagnetic exchange Heisenberg kagome model have shown that the large degeneracy associated with the 120…”
Section: 8mentioning
confidence: 99%
“…The most popular compound for use as the antiferromagnet in spin valves for magnetic recording is IrMn 3 , which in its ordered crystalline fcc phase is composed of ABC stacked [111] planes of magnetic Mn ions on kagome sites. 4,5,[11][12][13][14][15] The large number of studies over the past few decades on the near-neighbor antiferromagnetic exchange Heisenberg kagome model have shown that the large degeneracy associated with the 120…”
Section: 8mentioning
confidence: 99%
“…The geometry of intersecting {111} kagome planes describing the fcc kagome lattice offers earlier work that involved only NN exchange. 14 . Earlier DFT calculations 10,12 indicate that exchange up to fourth nearest neighbors are substantial in this transition-metal ion conductor that has been widely used as the exchange pinning antiferromagnetic thin film which is integral to spin valve technology.…”
Section: Discussionmentioning
confidence: 99%
“…We study the impact of the single ion and exchange anisotropies on the spin-wave fluctuations about the ground state configurations by considering the planewave solutions of the linearized spin torque equations. In order to perform the spin-wave analysis, it is convenient to introduce a local coordinate system on each sublattice site such that the equilibrium directions of the spins coincide with the z−components of the local coordinates [46]. This is done with the use of six transformation matrices, Λ i , which allow one to transform the local spin coordinates into the global ones: S i (r, t) = Λ i Si (r, t).…”
Section: Spin-wave Excitationsmentioning
confidence: 99%
“…The solutions of the linearized equations of motion (10) correspond to three spin-wave modes. When only isotropic exchange interaction are present in the system, all three modes are gapless with a single dispesionless mode, which reflects the macroscopic degeneracy of the 120 • ground state [46][47][48]. Intraplanar NN DM coupling (D 2 ) lifts the energies of two of the modes resulting in one acoustic and two optical modes [48].…”
Section: A Single Layermentioning
confidence: 99%